Local Development Planning in Nepal: Does it Actually Reflect Citizen Participation? - Gupta, Anil Kumar (Journal of Management and Development Studies, 2021)
Active participation and meaningful engagement of citizens in local development planning and discussion are the prime agendas of development governance in Nepal. Both state and non-state actors have placed great emphasis on citizen participation in local development planning and discussion through their plans, policies, and programmes. However, evidence shows that there is a low level of citizen participation and engagement. It is worrisome that these policies, plans, and programmes adopted by the state and non-state actors have not been able to deliver the expected results. In this regard, this paper aims to analyse citizen participation in local development planning and discussion. For this, it used the evidence generated by Nepal National Governance Survey 2017/18 and analysed the data using the logistic regression model. The results indicate that the degree of citizen participation in local development planning and discussion is relatively low. Nearly 30 percent of citizens reported that they participated in the local development planning and discussion in the past. It is remarkable to note that citizen participation varies according to their background characteristics.